2021
DOI: 10.1128/jvi.00528-21
|View full text |Cite
|
Sign up to set email alerts
|

CADM1 and CADM2 Trigger Neuropathogenic Measles Virus-Mediated Membrane Fusion by Acting in cis

Abstract: Measles virus (MeV), an enveloped RNA virus in the family Paramyxoviridae , is still an important cause of childhood morbidity and mortality worldwide. MeV usually causes acute febrile illness with skin rash, but in rare cases persists in the brain, causing a progressive neurological disorder, subacute sclerosing panencephalitis (SSPE). The disease is fatal, and no effective therapy is currently available. Although trans-synaptic cell-to-cell transmission is thought to account for MeV p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
1
19
0
1
Order By: Relevance
“…In some cases the virus can obtain hyperfusogenic mutations allowing it to spread from microglia to neuron and subsequently from neuron to neuron. Spread into neurons can be facilitated independent of CD150 or nectin-4 by cis- interaction of CADM1 and CADM2 on infected neurons, allowing virus transmission to interacting neurons [ 54 ]. Alternatively, spread into neurons can be dependent of nectin-4 through transfers of cytoplasmic cargo from infected epithelial cells to nectin-1-expressing neurons [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases the virus can obtain hyperfusogenic mutations allowing it to spread from microglia to neuron and subsequently from neuron to neuron. Spread into neurons can be facilitated independent of CD150 or nectin-4 by cis- interaction of CADM1 and CADM2 on infected neurons, allowing virus transmission to interacting neurons [ 54 ]. Alternatively, spread into neurons can be dependent of nectin-4 through transfers of cytoplasmic cargo from infected epithelial cells to nectin-1-expressing neurons [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In MeV infection, there is a late complication called subacute sclerosing encephalitis (SSPE) that arises from persistent infection in the brain, and viruses isolated from patients with SSPE have mutant fusion (F) proteins with high fusion ability. These mutant F proteins with high cell fusion ability are expressed on the same cells as cell adhesion molecule (CADM) 1 and 2 (called “cis” interactions), leading to cell fusion through the binding actions of these molecules 122,123 . Because these mutant F proteins differ in ability from the field strains, 124 it remains unclear whether natural morbillivirus infection in the CNS utilizes a similar mechanism.…”
Section: Pathology Of Morbillivirusesmentioning
confidence: 99%
“…These mutant F proteins with high cell fusion ability are expressed on the same cells as cell adhesion molecule (CADM) 1 and 2 (called "cis" interactions), leading to cell fusion through the binding actions of these molecules. 122,123 Because these mutant F proteins differ in ability from the field strains, 124 it remains unclear whether natural morbillivirus infection in the CNS utilizes a similar mechanism. However, experiments using F proteins isolated from patients with measles inclusion body encephalitis (F proteins containing a mutation for high cell fusion capacity) showed that MeV strains with these mutated F proteins caused CNS invasion through the respiratory route, 125 suggesting that the cell fusion capacity of the F protein is related to its neuropathogenic potential.…”
Section: Pathology Of the Six Species Of Morbilliviruses Except Femvmentioning
confidence: 99%
“…In addition, a novel molecular mechanism was described recently, where host cell adhesion molecules 1 (CADM1) and 2 (CADM2) interact in cis with MeV H in neurons as well as in other cells lacking SLAM and nectin-4, thereby allowing membrane fusion and cell-to-cell trans-synaptic spread. 33 Given that similar studies have not been conducted in CeMV-infected neurons, caution should be taken before crediting the striped dolphin BOFDI as a comparative model for human SSPE and SSPE-like neuropathies. Nonetheless, a detailed analysis of P, M, F, and H gene mutations in circulating CeMV isolates traceable to BOFDI cases will be helpful to shed light on how CeMV spreads and persists in the cetacean brain (Figure 1b).…”
Section: Priority 2: Molecular Basis For Different Disease Phenotypes During Cemv Infectionmentioning
confidence: 99%